A novel method of shrimp blanching by CO2 heat pump: Quality, energy, and economy analysis. (December 2022) - Zhang, Peng; Huang, Zhidian; Xu, Peng; Zhao, Dandan; Li, Xiaoqiong; Yang, Junling; Zhang, Zhentao; Lin, Jiahui; Li, Hanyong
Abstract: To reduce the energy consumption of the shrimp blanching process and improve the economic value of the blanched product, a transcritical CO2 heat pump blanching system (THPB system) was designed in this paper. The trends of astaxanthin were investigated at atmospheric pressure near boiling temperature, combined with the color and structural properties of shrimp samples, and the optimal blanching times of 270 s and 240 s were obtained at 90°C and 95°C, respectively. In contrast to the fuel blanching system (FB system) at 100°C, the annual standard coal consumption of the THPB system with 90°C blanching is decreased by 79%, and the annual operating cost can be saved by CNY 63, 800, with a payback period of about 3.13 years. Industrial relevance: Blanching is one of the effective ways to prolong the shelf life of shrimp. However, the research on the blanching time and temperature of shrimp is not comprehensive. In addition, the traditional fuel blanching process has high energy consumption and pollution, and can no longer meet the quality requirements of the modern food processing industry. Heat pump has been shown to have better performance in food drying, but it is less used in blanching. The information presented in this study may provide other insights into food processing. Highlights: A novel method of blanching shrimp is proposed with CO2 heat pump system. The blanched shrimp can also obtain higher quality with temperature below 100°C. The optimal blanching time at 90°C and 95°C is 270 s and 240 s respectively. The energy consumption of THPB system could decrease by 79% than FB system. The annual operating cost of THPB system can be saved by CNY 63, 800.